2007
DOI: 10.1111/j.1478-3231.2007.01459.x
|View full text |Cite
|
Sign up to set email alerts
|

Viral load 1 week after liver transplantation, donor age and rejections correlate with the outcome of recurrent hepatitis C

Abstract: Early post-LT HCV-RNA correlates with the severity of hepatitis C recurrence and in combination with donor age (>60 years) and rejections, identifies patients with a high risk of severe recurrence and candidates of cost-effective pre-emptive antiviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 37 publications
1
14
1
Order By: Relevance
“…Our results showed that Hepatitis C viral load before and after transplant (3–6 months) is highly significant factors affecting HCV recurrence after liver transplantation ( P < 0.003 and P < 0.001 resp.). In this context, the current results support earlier reports of Khettry et al [30] and Ciccorossi et al [31] that high viral load pre-LT was correlated with more progressive recurrence of HCV and higher early (1 week) posttransplantation viral loads (≥2.5 × 10 5  IU/mL) are at risk for significant recurrent hepatitis C. These data suggest that patients who are at risk for significant HCV recurrence can be identified early.…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that Hepatitis C viral load before and after transplant (3–6 months) is highly significant factors affecting HCV recurrence after liver transplantation ( P < 0.003 and P < 0.001 resp.). In this context, the current results support earlier reports of Khettry et al [30] and Ciccorossi et al [31] that high viral load pre-LT was correlated with more progressive recurrence of HCV and higher early (1 week) posttransplantation viral loads (≥2.5 × 10 5  IU/mL) are at risk for significant recurrent hepatitis C. These data suggest that patients who are at risk for significant HCV recurrence can be identified early.…”
Section: Discussionsupporting
confidence: 91%
“…Many variables can impact patient and/or graft survival (12, 13, 1623). In this study, we found recipient and donor age, female recipient gender, and treatment for acute rejection were also associated with severe fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Donation following cardiac death, donation from older individuals, or from those with steatotic livers is becoming an increasingly common practice around the world 15‐17. The reports demonstrating that advanced donor age is associated with more aggressive recurrence of HCV and early allograft failure in HCV‐positive liver transplant recipients highlights the need to evaluate the quality of hepatocytes from various donor sources, particularly those harvested from the livers of individuals selected on the basis of extended donor criteria 4, 18, 19. Such reports are consistent with our data, demonstrating that hepatocytes isolated from older donors (≥60 years) had lower viability and posttransplant engraftment ( P ≤ 0.01).…”
Section: Discussionmentioning
confidence: 99%